Effect of Surfactant Concentration on the Entrapment Efficiency Niosomes Aqueous Extract of Cassava Leaves (Manihot esculenta Crantz) - Hichmah, Hilmy Nur (Asian Journal of Pharmaceutics (AJP), 2019)
Context: Aqueous extract of cassava leaves (Manihot esculenta Crantz) has a high rutin content. Rutin has benefits as an antioxidant, anti-inflammatory, analgesic, and antidiabetic. The plant extract has low bioavailability and has a large molecular weight. Therefore, a carrier system like niosomes is required to allow aqueous leaves extract of cassava through to absorb in the body. Aims: The purpose of this study was to determine the effect of variation concentration of Span 40 that can trap aqueous extract of cassava leaves in niosomes optimally. Materials and Methods: Niosomes were done by thin-layer hydration method with concentration of Span 40 which was varied into three formulas: Formula A (100 Î¼mol), Formula B (150 Î¼mol), and Formula C (200 Î¼mol). Statistical Analysis Used: The data analysis using SPSS analyzed by one-way ANOVA. Results: The rutin contained in cassava leaves of this research is 42.52%. Entrapment efficiency test used dialysis membrane method and the result showed that the increased concentration of Span 40 is used; the entrapment efficiency is also increasing. The result of SPSS test using one-way ANOVA of three formulas did not show significant difference (P > 0.05). Conclusions: Optimum concentration of Span 40 in trapping aqueous extract of cassava leaves is Formula A (100 Î¼mol) which was 95.9%.